A Preliminary Study of the Mechanical Performance of a Novel FBG-Based Flexible Stress Sensor - Bi, Gang; Yang, Long; Li, Fan (Salehan Institute of Higher Education, 2026)
Soil stress monitoring is critical for accurate soil state assessment in geotechnical engineering, yet conventional resistance-based stress sensors—typically encapsulated in rigid materials—often generate measured values deviating upward from analytical solution predictions, limiting their practical reliability. To address this key limitation, this study aims to propose a novel fiber Bragg grating (FBG)-based flexible stress sensor that integrates the high precision of FBG technology with the adaptive conformability of flexible sensing platforms. For validation, systematic physical modeling tests were conducted using multiple soil types (clay and sand) under different loading protocols, where the proposed sensor’s performance was comprehensively compared with that of a conventional resistance-based rigid sensor. Key findings reveal that the FBG-based flexible sensor delivers more accurate stress measurements in both clay and sand; notably, during cyclic loading within the elastic range, it reverts to its initial state with minimal hysteresis, outperforming the rigid counterpart in dynamic stability. The novelty of this work lies in the fusion of FBG sensing with flexible encapsulation, which mitigates the overestimation issue of rigid sensors and enables more reliable soil stress monitoring for geotechnical applications.